2016
DOI: 10.5937/zasmat1601081s
|View full text |Cite
|
Sign up to set email alerts
|

Research of properties of nanoscopic structures

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…But it is also established that poor conductors (under normal conditions) are at the same time the best superconductors, and vice versa [4,[15][16][17][18][21][22][23]. Against this background, it can be concluded that in the spatially very limited structures the best superconducting properties can be expected, or that restriction of the spatial dimensions of the structure plays a major role in improving superconducting properties of material.…”
Section: Discussionmentioning
confidence: 99%
“…But it is also established that poor conductors (under normal conditions) are at the same time the best superconductors, and vice versa [4,[15][16][17][18][21][22][23]. Against this background, it can be concluded that in the spatially very limited structures the best superconducting properties can be expected, or that restriction of the spatial dimensions of the structure plays a major role in improving superconducting properties of material.…”
Section: Discussionmentioning
confidence: 99%
“…For positive results in this area, many more experimental methods are used. Even those theoretical mainly represent the results obtained using the computing resources, as opposed to analytical methods [20][21][22][23][24][25][26][27].…”
Section: Potential Research Of Core Ultrathin Multi-shell Nanodelivermentioning
confidence: 99%
“…Tipični predstavnici ovako dobijenih film-struktura su molekulski kristali, kod kojih se javljaju elementarna pobuđenja -eksitoni, u rezultatu interakcije spoljaš-njeg promenljivog elektromagnetnog polja i elektrona kristala. Eksitonski koncept definiše dielektrična, optička (apsorpcija, disperzija svetlosti, luminescencija), fotoelektrična i slična svojstva kristala, te se upravo zbog toga javio interes za izučava-njem eksitonskog podsistema u nanoskopskim strukturama [8]. Pomoću eksitonskog zakona disperzije i njihove gustine stanja, teorijski se definiše relativna permitivnost, a preko nje i optičke osobine posmatranog sistema.…”
Section: Uvodunclassified